jMonkeyEngine 3.0 beginner's guide: develop professional 3D games for desktop, web, and mobile, all in the familiar Java programming language - Kusterer, Ruth (PACKT Publishing, 2013)
With plenty of practical examples, screenshots and example code, create a complete game step by step. Learn by doing. Less theory, more results,If you have an inventive mind, are experienced in Java, enjoy looking through the smoke and mirrors of VFX and the world of game mechanics then this book is for you.